Use of Advanced Imaging Techniques for the Characterization of Oily Skin - Maia Campos, Patricia M. B. G.; Melo, Maisa O.; Mercurio, Daiane G. (Frontiers in Physiology, 2019)
The oily skin presents clinical signs that cause discomfort to patients, as excessive shine, enlarged pores and acne, which, in addition to an imbalance of the hydrolipidic layer. In this context, there is a constant demand in the cosmetic and dermatological area for the Research and Development of products that prevent these features. Thus, the objective of this study was to evaluate the cutaneous characteristics of oily skin due an excessive production of sebum through biophysical and skin imaging techniques. 19 participants with different skin types were selected and the following parameters were evaluated: pore count, determination of the number of sebaceous glands and amount of sebum in infundibulum, determination of cutaneous microrelief, count of comedones, evaluation of epidermis thickness, characterization of the cellular and comedones size and characteristics. These evaluations were done through biophysical and skin imaging techniques. The obtained results showed that the different regions of the face presented different characteristics related to oiliness, quantity and appearance of pores and comedones. The malar region had a lower epidermis thickness and a larger number of large pores. Moreover, in this region was noted an excessive production of sebum which can be related to a presence of pores, not comedones. The nose region presented higher sebum content in the infundibulum and lower active sebaceous glands, showing a higher activity of sebaceous production in this region. The chin region presented a positive correlation between the sebum content and the roughness parameter and the number of pores and comedones. As different skin properties are related and influence the appearance of undesirable clinical signs, we can evidence a need for a multifactorial approach to an effective treatment of oily skin. The rational development of multifunctional cosmetic products that promote the control of oily skin, regulating the keratinization process, improving the microrelief and leading to a better epidermis and dermis structure, will not only improve oily skin conditions but will also allow the reduction or disappearance of clinical signs resulted from excessive oiliness, which is great cause of concern and search for cosmetic and dermatological products due to their unaesthetic nature.